Case Report: α-amanitin toxicosis leading to acute death in a puppy - Lake, Zachary; Ludwik, Tasia; Hake, Caylie (Frontiers in Veterinary Science, 2025)
A 12-week-old, male intact, Shetland Sheepdog presented with acute onset vomiting and diarrhea, rapidly progressing to stupor and hypoglycemic shock following ingestion of α-amanitin-containing mushrooms. Despite aggressive therapeutic interventions, the patient exhibited rapid systemic deterioration characterized by recurrent hypoglycemia, hypotension, and multi-organ failure, leading to cardiopulmonary arrest within 22 h of presentation. Definitive diagnosis was unable to be elucidated prior to death, leading to an untailored treatment plan. Post-mortem analysis confirmed extensive necrosis of the liver, kidneys, and brain. Presence of α-amanitin was confirmed in the hepatic tissue via post-mortem liquid chromatography–tandem mass spectrometry analysis. Serum collected at presentation was submitted post-mortem for an insulin level which was found to be discordantly elevated, which may demonstrate an alternative mechanism of hypoglycemia in this case. This case highlights the rapidly lethal potential of α-amanitin in pediatric patients and the non-classical case presentation. This report contributes to the limited veterinary literature on this toxin in pediatric patients and underscores the need for heightened awareness and rapid diagnosis and treatment in suspected cases.